Selecting brand elements - a theoretical model for developing brand personality - García García, Antonio Isaac; Díaz-Casquero, Álvaro (AEMARK, 2023)
This study presents a theoretical framework for start-ups to correctly manage the elements of their brand and develop their brand personality. It highlights the importance of brand personality in connecting with the intended audience and offers evidence-based guidelines for selecting appropriate brand elements, such as color, name, and font, to achieve desired goals. The research methodology involved several key steps, including the development of a theoretical model called "Brand Personality Process Management" through a comprehensive review of the relevant literature. This model aims to illustrate the correct process of creating a new brand by taking advantage of potential growth areas and provides a framework for conveying specific personality traits through different brand elements. The reliability of this model was verified through the participation of two focus groups. In conclusion, this study offers valuable information on effective branding strategies for start-ups seeking to establish themselves in competitive markets.
Keywords: Logotipos; Marcas registradas; Diseño tipográfico; Brand personality; Brand strategy; Logo; Brand management